Design and development of the aluminium-air battery - Yong, Cheng Jie (2021)
Lithium-ion is have problem with its raw material availability and recyclability, lithium ion battery also have high cost and have safety concern. Although all this con for Lithium battery, it is still the dominant energy-storage technology for many application. Iron, zinc, magnesium, and aluminium, are some of the best material to be incorporate into the future batteries because of their abundance, capability of recyclability, low weight, cheap cost, and multiple electron redox properties. All this metal can be used as metal negative electrodes for metal–air batteries. Among the metal-air battery, the aluminium-air (Al-air) battery is candidate of next generation battery, especially in the field of electrical vehicles due to the high theoretical energy density (8100 Wh kg-1) Al-air batter have, which is much higher than the best performing lithium-ion batteries (LIBs). In this project, an Al-air battery is being design and developed which consist of aluminium anode, air cathode, and electrolytes with casing. The material used for each component is being researched, compared and selected. The different manufacturing process of the battery is also being compared and the most viable method is used to build the battery. The cost of the material and manufacturing is also being look in to and the most cost efficient way to fabricate the unit was being used. Polarization test and discharge test were conducted using a VersaSTAT 4, a device which consist of the function of Potentiostat and Galvanostat to analyses the performance of the battery build. The battery build have an open circuit voltage of 1.2V per cell, higher voltage is achieve by connecting the cell together, a three cell battery is build and have an open circuit voltage of 3.5V. The single cell battery can give off a maximum power of 0.015W and have a 175mAh capacity.